Sets that are connected in two random graphs. Issue 3 (13th March 2013) - Molloy, Michael
ABSTRACT –We consider two random graphs G1, G2, both on the same vertex set. We ask whether there is a non‐trivial set of vertices S, so that S induces a connected subgraph both in G1 and in G2. We determine the threshold for the appearance of such a subset, as well as the size of the largest such subset. © 2013 Wiley Periodicals, Inc. Random Struct. Alg., 45, 498–512, 2014